2007
DOI: 10.2174/138955707782795610
|View full text |Cite
|
Sign up to set email alerts
|

Glycodendrimers as Anti-Adhesion Drugs Against Type 1 Fimbriated E. coli Uropathogenic Infections

Abstract: Bacterial drug resistance against antimicrobial agents is a prevalent and central worldwide impasse. Infections with resistant organisms lead to adverse clinical outcomes, increased mortality, and are costly to healthcare systems. Several infectious diseases are initiated by the binding of pathogenic lectins to host cells glycoconjugates. The molecular understanding of these adhesion phenomena is crucial and presents promising new alternatives compared to traditional antibiotic therapies. Glycans or glycan mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 37 publications
3
74
0
Order By: Relevance
“…These results, obtained with multivalent glycomimetics as ligands of FimH and as inhibitors of type 1 fimbriae-mediated adhesion of E. coli, [32,33,43] are not in accordance with the monovalent nature of the fimbrial lectin, though. In addition, clustering of several FimH CRDs by typical multivalent glycomimetics is unlikely, given the size of fimbriae and their distance dimensions on the bacterial surface.…”
Section: Special Approaches To the Inhibition Of Mannose-specific Bacmentioning
confidence: 95%
See 1 more Smart Citation
“…These results, obtained with multivalent glycomimetics as ligands of FimH and as inhibitors of type 1 fimbriae-mediated adhesion of E. coli, [32,33,43] are not in accordance with the monovalent nature of the fimbrial lectin, though. In addition, clustering of several FimH CRDs by typical multivalent glycomimetics is unlikely, given the size of fimbriae and their distance dimensions on the bacterial surface.…”
Section: Special Approaches To the Inhibition Of Mannose-specific Bacmentioning
confidence: 95%
“…Their synthesis and testing results as inhibitors of UPEC has recently been reviewed in detail. [43] Mannose Glycoclusters with Noncarbohydrate Core…”
Section: Multivalent Glycomimetics As Inhibitors Of Type 1 Fimbriae-mmentioning
confidence: 99%
“…This knowledge can be utilized when FimH antagonists are designed. 7,11 In addition, mannopyranosides with a rather extended aglycon moiety have often shown enhanced binding affinity, [18][19][20] but in this case no conclusive interpretation of structure-activity relationships has been achieved. The same is true for multivalency effects that have frequently been observed with miscellaneous cluster mannopyranosides as ligands for type 1 fimbriated bacteria, especially with bi-and trivalent glycoclusters.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Amongst these, the early hyperbranched l-lysine scaffold, prepared by solidphase peptide and Fmoc chemistry, was elongated with Nchloroacetylglycylglycine and efficiently coupled to an Nacryloylated para-aminophenyl a-d-mannopyranoside [35] to provide octamer 19 (IC 50 2.8 nm (22.4 nm/Man)) (Scheme 2). It was found that a competitive binding assay measuring the binding of 125 I-labeled, highly mannosylated neoglycoprotein (BSA) to the type 1 fimbriated Escherichia coli (K12) strain in suspension gave much lower IC 50 values than the equivalent values obtained by hemagglutination or in assays that [a] Relative potency for the inhibition of binding of E. coli to epithelial cells.…”
Section: Introductionmentioning
confidence: 99%